2017
DOI: 10.1007/s00701-017-3106-3
|View full text |Cite
|
Sign up to set email alerts
|

Prechiasmatic sulcus and optic strut: an anatomic study in dry skulls

Abstract: The present study augments the current knowledge of the morphology of key anatomical landmarks, prechiasmatic sulcus and the optic strut, for cavernous sinus surgery and indicates population and gender differences. We report significant anatomical variations in the prechiasmatic sulcus, optic strut and surrounding structures. In addition to providing a better understanding of the anatomical landmarks, necessary for the safe navigation in transcranial and endoscopic procedures, the present results also suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…7 In our study postsulcal variant was least common variant observed and sulcal variant was the most common variant observed similar to the above study. The majority of optic struts were observed to be attached to the anterior 2/5 of the anterior clinoid process (ACP) in both Korean and Indian populations, as reported in studies by Kanellopoulou et al 5 A study by Kapur and Mehic analysed on 200 dry human skulls of both sexes including 109 males and 91 females yielded similar findings, with 42% on the right side and 47.8% on the left side showing this attachment pattern. 12 Menasinkai and Savitha conducted another research study on 37 dry skulls, and their results were consistent (45.95% on the right side and 37.83% on the left side) with those of Kanellopoulou et al and Kapur and Mehic.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…7 In our study postsulcal variant was least common variant observed and sulcal variant was the most common variant observed similar to the above study. The majority of optic struts were observed to be attached to the anterior 2/5 of the anterior clinoid process (ACP) in both Korean and Indian populations, as reported in studies by Kanellopoulou et al 5 A study by Kapur and Mehic analysed on 200 dry human skulls of both sexes including 109 males and 91 females yielded similar findings, with 42% on the right side and 47.8% on the left side showing this attachment pattern. 12 Menasinkai and Savitha conducted another research study on 37 dry skulls, and their results were consistent (45.95% on the right side and 37.83% on the left side) with those of Kanellopoulou et al and Kapur and Mehic.…”
Section: Discussionsupporting
confidence: 66%
“…4 Optic strut and Prechiasmatic sulcus are important anatomic landmarks for accessing ophthalmic artery aneurysms or tumors in the regions adjoining sella turcica. [5][6][7] OS along with the ACP are separated from the lesser wing of sphenoid to provide better access to Internal Carotid artery and cavernous sinus in cases of aneurysms or tumors involving cavernous sinus. [8][9][10][11] There is a paucity of studies on the morphometry of optic strut in the Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…14 For these reasons, anatomical variations of the structures including the CR may be important in terms of effective and successful surgical outcome. 5,6,8,13,20,21 Meningiomas localized in the suprasellar region may be removed with transcranial approaches from ''above,'' while with endoscopic transnasal approach from ''below.'' 8,12 The potential area beneath the CR poses a residual tumor risk during the removal of meningiomas using transcranial techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors localized in the suprasellar region may exhibit aggressive behavior, characterized by invasion of adjacent anatomical structures; in this case, technical difficulties may be encountered in the application of surgical approaches 14 . For these reasons, anatomical variations of the structures including the CR may be important in terms of effective and successful surgical outcome 5,6,8,13,20,21 …”
Section: Discussionmentioning
confidence: 99%